Investigation the influence of ar plasma treatment on cell response for wet-spun starch/polycaprolactone fiber mesh scaffolds - Tuzlakoglu, Kadriye (2008)
In design of a tissue engineering scaffold, surface physicochemistry is one of the most important issues to be considered. The physicochemical properties of the surface directly influence the scaffold performance by affecting the cellular response and ultimately effecting the new tissue formation. In order to improve the cell affinity, the surface hydrophiliticy, surface energy, surface roughness and surface charge can be modify by different methods. Plasma treatment is a versatile method for surface treatment of biodegradable polymers without altering their bulk properties. By this method, it is possible to introduce or graft desired functional groups onto the surface. This study aims to investigate the influence of Ar plasma treatment on osteablast cell response for fiber mesh scaffolds from a starch-polycaprolactone blend. [...]